Personalized Dosing of Dichloroacetate Using GSTZ1 Clinical Genotyping Assay - Langaee, Taimour; Wagner, Richard; Horne, Lloyd P; Lawson, Lee Ann; Becker, Cecilia; Shahin, Mohamed; Starostik, Petr; Stacpoole, Peter W (Genetic testing and molecular biomarkers, 2018)
Dichloroacetate (DCA) represents the first targeted therapy for pyruvate dehydrogenase complex deficiency; it is metabolized by glutathione transferase zeta1 (GSTZ1). Variation in the GSTZ1 haplotype is the principal variable influencing DCA kinetics and dynamics in humans. We aimed to develop a sensitive and rapid clinical genetic screening test for determining GSTZ1 haplotype status in individuals who would be treated with DCA, and then apply the test for the investigation of the plasma pharmacokinetics (PK) of DCA as a function of GSTZ1 haplotype. DNA samples from 45 healthy volunteer study participants were genotyped for three functional GSTZ1 single nucleotide polymorphisms (rs7975, rs7972, and rs1046428) by TaqMan . Prior studies showed that subjects with at least one EGT haplotype (EGT carrier) metabolized DCA faster than EGT noncarriers. The clinical genetic test for GSTZ1 was developed and validated at our CLIA-certified Clinical Laboratory. Four fast metabolizer EGT carriers and four slow metabolizer EGT noncarriers were selected to complete a standard PK study. Each participant received a single oral dose of 25 mg/kg of DCA (IND 028625) for 5 days. The EGT haplotype carrier group demonstrated significantly faster metabolism of DCA and higher rates of plasma DCA clearance after 5 days of drug exposure compared with EGT noncarriers (p = 0.04). These preliminary data establish the validity and practicality of our rapid genotyping/haplotyping procedure for genetic-based DCA dosing to mitigate or prevent adverse effects in patients treated chronically with this drug.